Applied Research in Low-Income Countries: Why and How? - Acharya, Krishna Prasad; Pathak, Santosh (Frontiers in Research Metrics and Analytics, 2019)
Research and development (R&D) offers promising clues to address wide range of socioeconomic problems through development of new products and services or often by improving the existing ones. High income countries have realized the worth of R&D and invested tremendously in that sector; however, resource-poor low income countries (LICs) are far behind in realizing the potential benefit that R&D could offer towards economic growth and national development. Even if some LICs have positive outlook towards R&D sector, the trend of emulating works from HICs to solve local or regional issues have most often yielded counterproductive results. LICs are suggested to primarily focus on applied research by incorporating their socioeconomic and cultural aspects to solve their everyday problems whose investigation is often ignored in research intensive nations. Moreover, applied research in LICs offers the potential to provide low-cost and innovative solutions to local and/or regional problems with global implications.